EE319 Healthcare resource utilization and direct medical costs associated with post COVID-19 condition in Colombia, 2020-2021 (2023)
Objectives. This study aimed to estimate the direct medical costs of patients with post COVID-19 condition in a Colombian insurance company with more than 2.5 million affiliates. Methods. We conducted a bottom-up cost-of-illness study of adults with persistent symptoms after at least three months of hospital discharge due to COVID-19. We surveyed patients that were hospitalized between March 2020 and August 2021. We asked about healthcare resource utilization (HCRU), which included laboratories and images, medications, consults, rehospitalizations, and others, associated with post COVID-19 condition. The answers were verified using the company’s outpatient and inpatient service authorization records. Costs were estimated from the third payer perspective and expressed in American dollars using an exchange rate of 1USD$=3,743COP. Results. We included 202 participants, 51.5% were male, mean age of 55.6 years old, 49% had a comorbidity (41.9% hypertension), and 46 patients (22.8%) required an intensive care unit. A total of 159 (78.7%) patients reported at least one symptom after discharge. Of these, 132 (65.3%) persisted with at least one symptom during the telephone survey. Seventy-five (47.2%) of the 159 patients with persistent symptoms reported HCRU. Of these, 93.3% consulted a physician (mean consultations: 2.1 SD 1.1; mean consultations with specialists: 2.4 SD 2.0), and 9.3% were re-hospitalized. The average direct medical costs of post COVID-19 condition were US$824 (95%CI 195-1,454). Costs in outpatient were US$373 (95%CI 158-588), and in inpatient, US$3,285 (95%CI -167-6,738). Conclusions. It is crucial to follow up and identify patients discharged from the hospital who persist with symptoms after three months since we observed a greater HCRU, including prolonged recovery therapies